On α ̌–φ ̆-Fuzzy Contractive Mapping in Fuzzy Normed Space - Raghad I. Sabri; Buthainah A. A. Ahmed (مجلة بغداد للعلوم, 2023)
The idea of fixed points represents one of the most potent mathematical tools. This paper's main purpose is to introduce a new kind of fuzzy contractive mapping in a fuzzy normed space (briefly  space) namely "fuzzy contractive mapping". We proved some fixed point results for this mapping in the setting of  space using the triangular property of fuzzy norm. Moreover, under specific conditions, some other results for such type of mapping are established. Finally, an example is offered to show the results' usefulness.